Analysis of Fan Component Maintenance in the Cement Mill of PT Semen Padang Indarung V Factory using the Reliability Centered Maintenance Method Approach - Almeiwiyanto, Nendar; Sulaeman (Jurnal Teknik Mesin, 2023)
The impact of environmental air pollution is causing a decrease in air quality which has a negative impact on human health. The size of dust particulates that endanger general health ranges from 0.1 micro to 10 micro. In general, the size of dust particulates of around 5 micro is airborne particulates that can directly enter the lungs and settle in the alveoli. The impact on the life time of one of the components in the mill fan is the presence of dust as a polluting element in the impeller, therefore a particulate device is needed. Miil Fan requires continuous and scheduled maintenance so that the tool works optimally. If damage occurs in these two parts, the final process of making cement will stop. Then the Reliability Centered Maintenance (RCM) method was chosen, which is a systematic process used to determine what must be done to ensure that each physical facility of the company can comply with the design function continuously within a certain period of operation. The components analyzed in RCM are critical components which were previously analyzed using the Failure Mode, Effect and Critically Analysis (FMECA) method. The components analyzed are components with a Risk Priority Number value >60 (above critically high status). Analysis of the fan engine (P05) shows that there are 3 critical components, namely the impeller, bearing and V-belt.